PRAKTIK KEPEMIMPINAN TRANSFORMASIONAL DAN IMPLIKASINYA TERHADAP KINERJA GURU: STUDI KASUS PADA SEKOLAH DASAR NEGERI DI KECAMATAN CURUG KOTA SERANG - Saipan Saipan; Ahmad Mukhlis; Andriani Andriani (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Teacher performance is the main determinant of learning quality in elementary schools, but its improvement does not always go hand in hand with curriculum reform and strengthening of education regulations. Recent studies have shown that principals' leadership plays a strategic role in shaping teacher commitment, innovation, and effectiveness, but leadership practices at the elementary school level still show variations in implementation and impact. This study aims to analyze the transformational leadership practices of school principals and their implications on teacher performance in State Elementary Schools in Curug District, Serang